2006
DOI: 10.1088/0264-9381/23/23/020
|View full text |Cite
|
Sign up to set email alerts
|

Emergent universe with exotic matter

Abstract: A general framework for an emergent universe scenario has been given which makes use of an equation of state. The general features of the model have also been studied and possible primordial composition of the universe have been suggested.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
272
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(276 citation statements)
references
References 22 publications
4
272
0
Order By: Relevance
“…This theorem was developed in 2003 by Arvind Borde, Alan Guth and Alex Vilenkin [8].Vilenkin's arguments demonstrate that null and time-like geodesics are generally incomplete in inflationary models, regardless of whether energy conditions are maintained, provided that the average expansion condition (H > 0) is maintained throughout of these geodesics directed towards the past. The search for cosmological models without initial singularities has led to the development of emergent universes models (UE) [9,10,11,12,13,14,15,16]. However, most simple models developed in a context of General Relativity suffer from instabilities, associated with the instability of Einstein's static universe [17].…”
Section: Introductionmentioning
confidence: 99%
“…This theorem was developed in 2003 by Arvind Borde, Alan Guth and Alex Vilenkin [8].Vilenkin's arguments demonstrate that null and time-like geodesics are generally incomplete in inflationary models, regardless of whether energy conditions are maintained, provided that the average expansion condition (H > 0) is maintained throughout of these geodesics directed towards the past. The search for cosmological models without initial singularities has led to the development of emergent universes models (UE) [9,10,11,12,13,14,15,16]. However, most simple models developed in a context of General Relativity suffer from instabilities, associated with the instability of Einstein's static universe [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature the late accelerating phase of the universe is obtained with exotic matter or with a modification of the Einstein gravity. A non-linear equation of state is also considered in the literature to construct cosmologies [13], emergent universe model is one such model. The Emergent universe (EU) model obtained by Mukherjee et al in the flat universe permits an accelerating phase.…”
Section: Introductionmentioning
confidence: 99%
“…EU scenario has been explored with quintom matter [16] and further investigated the realization of the scenario with a non-conventional fermion field to obtain a scale invariant perturbation [17]. It has been shown that the EU scenario can be implemented successfully in the framework of general relativity [13] in addition to Gauss-Bonnet gravity [18]. The modified Gauss-Bonnet gravity as gravitational alternative for dark energy is however considered by Nojiri and Oddintsov [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations